Key Performance Indicators in Construction Projects Identification, Development and Selection - STOCKENBERG, FELICIA; Sultán, Amanda (My University, 2018)
Measurement tend to make things happen by showing the progress and thereby motivate people to take action. Performance measurement can be used as a tool within an organization to connect the daily activities to the strategic objectives. Key Performance Indicators, KPIs, are indicators that focuses on performance directly linked to the most critical success factors within an organization and can indicate if the performance is in compliance with the strategic goals and objectives. The environment of construction projects is constantly changing, and the complexity of the projects contributes to a high level of uncertainties. By using measures, it is possible to track the causal factor behind the result and KPIs can dissolve organizational performance into a manageable number of indicators. The aim of this thesis is to identify, develop and select KPIs suitable for the production process of construction projects at Flodéns, which is a limited company in the construction sector. The selection of KPIs was delimited into a general, yet limited and focused KPI matrix which can be used to enable continuous monitoring of the production process to achieve project success and enable comparisons between projects. The selection of KPIs resulted in 13 KPIs intended to be measured during the production process, complemented by 9 KPIs intended to be measured in the final stage of the projects. However, there are aspects that must be considered when, or if, KPIs should be implemented. For example, measurement can lead to sub-optimization which can result in impaired performance. Additionally, estimations used as inputs can be manipulated to create good results if the focus is set on the result of the KPIs rather than the performance it-self. Finally, the KPIs must be used wholehearted to generate useful information. If not, the data collection and measurement will be of less quality and the KPI-values will be close to useless.
Keywords: Samhällsbyggnadsteknik; Civil Engineering